Effect of naoh concentration in alkaline sulfite anthraquinone and methanol pulping on Buluh Madu - Mohd Asri, Norsurehasuhada (2017)
The objective of this study was to determine the effect of pulp and paper properties of Buluh Madu using alkaline sulfite anthraquinone and methanol (ASAM) pulping at different NaOH concentration. Bamboo chips were cooked at three different levels of sodium hydroxide, namely 14, 16 and 18% for 90 minutes. Other pulping parameters that remained constant were the use of of 0.5% ethylene diamine tetraacetic acid (EDTA), with an 80/20 ratio Na2SO3/NaOH, 0.1% anthraquinone, 15% methanol and a temperature of 170°C in the cooking process. Samples prepared using 18% NaOH resulted in the highest pulp yield, 42.70%, and a Kappa number of 21.34. It seems that NaOH percentage significantly effect on the paper properties (tensile, tear and burst strength) and doesn’t much effect on the pulp properties (pulp yield, Kappa number and freeness). The high quality of bamboo pulp and paper produced by the ASAM pulping process was found to be beneficial for the use in paper and paperboard manufacturing.